Validity in educational & psychological assessment - Newton, Paul E.; Shaw, Stuart D., 1962-; Cambridge Assessment (Los Angeles : SAGE, 2014)
This book shows how the consensus view of validity was at best rather shallow. Notably, the consensus view leaves unresolved important tensions between those who see validation as a never-ending process (e.g., Cronbach, Messick) and those who understand the needs of those who produce assessments to be able to say that they have undertaken necessary due diligence to attest to the quality of assessments (e.g., Ebel, Kane). As well as providing an excellent, scholarly review of the history of the idea of validity, this book shows how a modified version of Messick's facet model of validity can produce a rigorously grounded, and yet practical, approach to assuring the quality of educational and psychological assessments.
Validity and validation -- The genesis of validity : mid-1800s-1951 -- The fragmentation of validity : 1952-1974 -- The (re)unification of validity : 1975-1999 -- The deconstruction of validity : 2000-2012 -- Twenty-first-century evaluation.
Published in association with Cambridge Assessment.
Includes bibliographical references (pages 227-245) and index.
Keywords: Examinations -- Validity; Educational tests and measurements -- Social aspects; Psychological tests -- Social aspects; Psychometrics -- Social aspects; Examinations -- Interpretation